2005
DOI: 10.1080/13546800344000327
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia, theory of mind, and persecutory delusions

Abstract: This study represents only the third demonstration of a specific link between paranoid delusions and ToM impairment. Reasons why previous findings on this issue have been so inconsistent are considered. Further research is needed to explore the relationships among paranoia, ToM, and length of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 30 publications
1
29
2
Order By: Relevance
“…Delusional patients also tend to rigidly hold their beliefs and refuse to consider any disconfirmatory evidence (Woodward, Moritz, Cuttler, & Whitman, 2006). In addition, these patients have trouble envisioning others' intentions or drawing plausible conclusions about the motives of others (Corcoran et al, 1995;Frith & Corcoran, 1996;Brune, 2005;Harrington, Langdon, Siegert, & McClure, 2005;, an ability widely known as Theory of Mind which has been defined as the "capacity to represent one's own and other persons' mental states" (Brune, 2005, p 21).…”
Section: Study Aimmentioning
confidence: 99%
“…Delusional patients also tend to rigidly hold their beliefs and refuse to consider any disconfirmatory evidence (Woodward, Moritz, Cuttler, & Whitman, 2006). In addition, these patients have trouble envisioning others' intentions or drawing plausible conclusions about the motives of others (Corcoran et al, 1995;Frith & Corcoran, 1996;Brune, 2005;Harrington, Langdon, Siegert, & McClure, 2005;, an ability widely known as Theory of Mind which has been defined as the "capacity to represent one's own and other persons' mental states" (Brune, 2005, p 21).…”
Section: Study Aimmentioning
confidence: 99%
“…However, not all studies have consistently replicated the specific relationship between ToM impairment and persecutory delusions. It has been suggested that these inconsistent findings may arise as a result of the nature of the tasks employed to assess ToM (Shryane et al, 2008;Corcoran et al, 2011), with some studies demonstrating that the relationship between ToM difficulties and positive psychotic symptoms is partially mediated by IQ (Harrington et al, 2005a). Furthermore, Freeman (2007) proposes the possibility of depression or grandiose ideation in people experiencing paranoia could have a role to play in the mixed ToM results and further research is warranted.…”
Section: Adults With Grandiose Delusionsmentioning
confidence: 96%
“…In a critical review by Bentall et al (2001), it was concluded that individuals with persecutory delusions perform more poorly than both psychiatric and non-psychiatric comparison groups on ToM tasks. Recently, Harrington, et al (2005a) reported that the ToM deficit was only observed in those participants with schizophrenia who also had persecutory delusions. Corcoran et al (2008) found poor performance on ToM tasks in adults with persecutory delusions irrespective of diagnosis and found that participants' performance was correlated with the degree of distress caused by this symptom.…”
Section: Adults With Grandiose Delusionsmentioning
confidence: 99%
See 2 more Smart Citations